2006
DOI: 10.1227/01.neu.0000223501.27220.69
|View full text |Cite
|
Sign up to set email alerts
|

Microanatomy of the Central Myelin-Peripheral Myelin Transition Zone of the Trigeminal Nerve

Abstract: The data definitively prove that the root entry zone (REZ, nerve-pons junction) and TZ of the trigeminal nerve are distinct sites and that these terms should never be used interchangeably. The measurements showed that the central myelin occupies only the initial one-fourth of the trigeminal nerve length. If trigeminal neuralgia is caused exclusively by vascular compression of the central myelin, the problem vessel would always have to be located in this region. However, it is well known that pain from trigemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 23 publications
3
61
1
Order By: Relevance
“…This area of the nerve differs from the more distal extent by being myelinated by oligodendroglia (16). This location of treatment has been thought to produce more reliable and possibly more long-lasting pain relief due to the radiation sensitivity of oligodendroglial myelin (15), although this remains controversial (14).…”
Section: Radiosurgery In the Initial Management Of Tnmentioning
confidence: 99%
“…This area of the nerve differs from the more distal extent by being myelinated by oligodendroglia (16). This location of treatment has been thought to produce more reliable and possibly more long-lasting pain relief due to the radiation sensitivity of oligodendroglial myelin (15), although this remains controversial (14).…”
Section: Radiosurgery In the Initial Management Of Tnmentioning
confidence: 99%
“…The axons of the root entry zone of the trigeminal nerve are coated with central nervous system myelin, which extends up to 5 mm along the root into the prepontine cistern. 10,26,27 In consequence, the junction between central nervous system myelin and peripheral nervous system myelin, which is approximately 2 mm in length, is located some distance away from the pons. Examination of trigeminal nerve roots from patients with compression of the nerve root by an overlying blood vessel has revealed focal demyelination in the region of compression, 10,27,28 which results in the abnormal generation of ectopic sensory impulses with subsequent spread to adjacent fibers, so that spontaneous nerve activity increases.…”
Section: Vascular Lesionsmentioning
confidence: 99%
“…The theory proposes that neuralgia occurs because of compression of the centralperipheral myelin transitional zone (TZ) of the trigeminal nerve by a vessel [15]. However, surgical decompression is not performed exclusively at this site in the case of TN.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on the length of the central myelin portion of the sensory root of the human trigeminal nerve [15,20]. Peker et al [15] revealed that the central-peripheral myelin TZ is located a mean of 1.13 mm from the REZ (the precise nerve-pons junction) on the medial aspect of the nerve, and 2.47 mm from the REZ on the lateral aspect. Therefore, central myelin demyelination can be extended to the cisternal segment, and is not limited to the REZ.…”
Section: Discussionmentioning
confidence: 99%